Automated System for Determination of Pupil Size Using Multispectral Imaging - Shanti, K J; Hegde, Bharatkumar; Shreya, P R; Chaitra, M M (2021 IEEE Bombay Section Signature Conference (IBSSC), 2021)
Pupil assessment has proved to be an indicator for deterioration of physiological and neurological conditions. The variation of pupil size in response to a light stimulus and its variation over a period could lead to understand the diabetic retinopathy as well. Development in the digital image capturing systems with infra-red LED's providing the stimulus paved way for the non-invasive method of pupil size determination. The procedural simplicity and the low-cost image capturing enables repeated studies critical for diagnosis. This paper discusses pupil detection and pupil diameter measurements using image processing algorithms implemented in OpenCV-Python